2009
DOI: 10.1016/j.pmrj.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay in Rehabilitation is Associated with Admission Neurologic Deficit and Discharge Destination

Abstract: Stroke remains one of the most common reasons for admission to acute care hospitals. The authors know of no studies that have examined the rehabilitation aspect of care incorporating the NIHSS in this manner. This study draws a connection between neurologic impairment by using the NIHSS and LOS and discharge destination in an acute inpatient rehabilitation stroke unit. In the future, multidisciplinary rehabilitation teams may consider using this measure to predict LOS and disposition at discharge from inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
2
21
0
2
Order By: Relevance
“…Patients with pLOS had significantly worse outcomes in nearly every measure. Of nonmodifiable risk factors, patients with pLOS had more severe neurologic dysfunction at baseline and were older than patients who did not experience pLOS, in keeping with previous reports [1, 35, 14]. Of modifiable risk factors, nonneurologic medical complications had the strongest association with pLOS.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with pLOS had significantly worse outcomes in nearly every measure. Of nonmodifiable risk factors, patients with pLOS had more severe neurologic dysfunction at baseline and were older than patients who did not experience pLOS, in keeping with previous reports [1, 35, 14]. Of modifiable risk factors, nonneurologic medical complications had the strongest association with pLOS.…”
Section: Discussionsupporting
confidence: 89%
“…IRF LOS contributes directly to the poststroke care cost. Studies have reported that patient severity (Appelros, ; Elwood et al., ; Harvey et al., ), negative symptoms (Galynker et al., ), medical complications (Saxena et al., ), and functional status at IRF admission (Brock et al., ; Franchignoni et al., ; Harvey et al., ; Stillman, Granger, & Niewczyk, ; Tan, Heng et al., ) are the major determinants of IRF LOS. Some other nonmedical patient characteristics and organization factors are associated with duration of IRF stay.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that after controlling for functional status at IRF admission and other covariates, a longer IRF LOS was associated with a higher Functional Independence Measure (FIM) total at IRF discharge ( p < .0001) but less likelihood to be discharged to the community (OR = 0.997, 95% CI = 0.994–0.999). In addition to medical conditions (Appelros, ; Elwood et al., ; Galynker et al., ; Harvey et al., ; Saxena, Koh, Ng, Fong, & Yong, ) and functional status at IRF admission (Brock et al., ; Franchignoni, Tesio, Martino, Benevolo, & Castagna, ; Harvey et al., ; Tan, Heng, Chua, & Chan, ; Stillman et al., ), other patient characteristics and nonmedical factors influence the duration of IRF stay, including patients’ socioeconomic status and family structure (Tan, Heng et al., ), caregiver characteristics and IRF discharge planning program (Tan, Chong, Chua, Heng & Chan, ), and incentives for cost containment and support inpatients’ home environments (Stineman et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the importance of discharge destination (17,18) (particularly to community hospitals and nursing homes) and adequacy of care by caregivers following discharge in determining the duration of the patient's hospital stay. In particular, the availability of caregiver assistance and support, (19) presence of dementia (20) and admission to intermediate and long-term care (ILTC) services (21) have emerged as the most significant factors.…”
Section: Introductionmentioning
confidence: 99%